Weight loss and body composition change among workers undergoing a meal replacement dietary program: feasibility and efficacy - Vigna, Luisella; Cossovich, A; Barberi, C; Sommaruga, D; Neri, L; Conti, D; De Simone, F; Agnelli, GM; Riboldi, L (Progress in Nutrition, 2016)
Introduction. Partial meal replacements supplementing low calorie diets may be convenient for working people in time-constrained occupational settings. However, there is limited data obtained among non-obese, otherwise healthy subjects and very few real-life clinical studies corroborating findings from clinical experiments.Methods. We evaluated weight loss, glycemic control and body composition change among volunteer workers undergoing a 4-week low calorie diet followed by a 4-week maintenance regimen supplemented with meal replacements products.Results. Forty-two employees took part to the study and completed the 4-week intervention, whereas 36 completed the maintenance phase. Thirty-one patients (73.7%) experienced a weight loss greater than 3% of initial body mass. There was a reduction in serum glucose (Δ28d= -6.9 mg/dL, p